Kebijakan Pengelolaan Aset dan Barang Milik Daerah di Pemerintah Provinsi Bali - I Gede Agus Wibawa; Dewa Ketut Suryawan (Universitas Warmadewa, 2025)
In fact, the issue of regional assets and property is a serious problem that must be handled well by all regional governments. The release or publication of one of the BPK RI auditors entitled